2018
DOI: 10.1364/oe.26.007005
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a heterostructured cladding solid-core photonic bandgap fiber for construction of Mach-Zehnder interferometer and high sensitive curvature sensor

Abstract: A heterostructured cladding solid-core photonic bandgap fiber (HCSC-PBGF) is designed and fabricated which supports strong core mode and cladding mode transmission in a wide bandgap. An in-line Mach-Zehnder interferometer (MZI) curvature sensor is constructed by splicing single mode fibers at both ends of a HCSC-PBGF. Theoretical analysis of this heterostructured cladding design has been implemented, and the simulation results are consistent with experiment results. Benefiting from the heterostructured claddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It is still difficult for a conventional PBG-PCF to achieve the co-existence of a vibrant core and cladding modes. Changing the arrangement of high refractive index rods can increase the confinement loss of the core mode with no obvious change in the band-gap position [18]. So, a microstructurally designed fiber is proposed to increase the confinement loss of the core mode to make sure that the energy can be effectively transferred to the cladding.…”
Section: The Theoretical Analysis and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still difficult for a conventional PBG-PCF to achieve the co-existence of a vibrant core and cladding modes. Changing the arrangement of high refractive index rods can increase the confinement loss of the core mode with no obvious change in the band-gap position [18]. So, a microstructurally designed fiber is proposed to increase the confinement loss of the core mode to make sure that the energy can be effectively transferred to the cladding.…”
Section: The Theoretical Analysis and Experimentsmentioning
confidence: 99%
“…The proposed MOF is fabricated in our laboratory [18]. The Ge-doped and pure silica rods are prepared with the diameter of 1 mm.…”
Section: The Theoretical Analysis and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-mode-area (LMA) fibers working with advanced mechanisms have been established as promising candidates for next-generation high-power fiber lasers, benefitting from their potentials in mode area scaling, higher nonlinear threshold, and feasibilities for some functional applications [1][2][3][4][5][6] . More recently, a kind of bandgap-guided microstructure fiber, called the allsolid photonic bandgap fiber (AS-PBGF), has become an emerging research focus [7][8][9][10][11][12] . Free of air-holes structures, AS-PBGF exhibits excellent practical convenience for the high-power platform [13] and portability for the double-cladding design or polarization-maintaining scheme [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2018) proposed a curvature fiber sensor based on the cascaded interferometers and the curvature sensitivity reached 4.362 nm/m −1 within 0-1.134 m −1 [6]. Hu et al (2018) reported a heterostructure cladding solid-core photonic bandgap fiber with a curvature sensing sensitivity of 24.3 nm/m −1 in the range of 0-1.75 m −1 [7]. Arrizabalaga et al (2020) used a multi-core fiber to achieve a sensitivity of 17.5 nm/m −1 as a curvature sensor [8].…”
Section: Introductionmentioning
confidence: 99%